Secret empires [compact disc, unabridged] : how the American political class hides corruption and enriches family and friends - Schweizer, Peter, 1964- (Harper Audio, 2018)
Peter Schweizer explains how a new corruption has taken hold, involving larger sums of money than ever before. Stuffing tens of thousands of dollars into a freezer has morphed into multibillion-dollar equity deals done in the dark corners of the world. President Donald Trump's children have made front pages across the world for their dicey transactions. However, the media has barely looked into questionable deals made by those close to Barack Obama, Joe Biden, John Kerry, Mitch McConnell, and lesser-known politicians who have been in the game longer.